2019
DOI: 10.33706/jemcr.601323
|View full text |Cite
|
Sign up to set email alerts
|

Acute mechanical intestinal obstruction due to foreign body ingestion

Abstract: Introduction: Foreign body ingestion usually occurs accidentally and is a common condition in childhood, but it is rarely seen in adults and is frequently encountered in people with mental retardation and psychiatric disease. The outcome is usually defecation of the ingested materials but rarely requires surgical intervention.Case Report: A 33-year-old male patient was admitted to the emergency department with the complaint of constipation as a result of swallowing about 1000 plastic buttons yesterday. His acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Foreign bodies in the upper gastrointestinal tract are most frequently observed in the esophagus and stomach. Foreign bodies are frequently seen in the lower gastrointestinal tract at the level of the ileum, where the lumen is relatively narrow [6,7,[11][12][13]. In our study, foreign bodies were most frequently observed in the ileum, duodenum, and stomach, which is compatible with the findings in the literature.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Foreign bodies in the upper gastrointestinal tract are most frequently observed in the esophagus and stomach. Foreign bodies are frequently seen in the lower gastrointestinal tract at the level of the ileum, where the lumen is relatively narrow [6,7,[11][12][13]. In our study, foreign bodies were most frequently observed in the ileum, duodenum, and stomach, which is compatible with the findings in the literature.…”
Section: Discussionsupporting
confidence: 91%
“…Ingested foreign bodies are frequently excreted naturally from the gastrointestinal tract without any complications [1,[12][13][14][15]. However, some complications may occur depending on the type of the foreign body, its characteristics (pointed, blunt tip), removal duration, and the number of objects.…”
Section: Discussionmentioning
confidence: 99%